Analysis of sexual and reproductive health indicators according sexual orientation young Brazilians'. (20th October 2021) - Sousa, M; Rocha, L; Silva, F; Felisbino-Mendes, M
Abstract: Background: Sexual and reproductive health indicators and behaviors may occur differently between sex and according to sexual orientation. In addition, there is a lack of studies that consider sexual orientation and approach young adults in Brazil. Objective: To analyze sexual and reproductive health indicators of young Brazilian adults and their differences according to sex and sexual orientation. Methods: Cross-sectional study with 2, 063 young adults, undergraduate students from a public university who responded to the online survey. We estimated the prevalence of sexual and reproductive health indicators, desire or not to have children, report of pregnancy and feeling about the pregnancy state), according to sex (male and female) and sexual orientation (heterosexual, bisexual, homosexual). Differences between prevalence were assessed using Pearson's chi-square test. Results: Among heterosexuals, condoms were the contraceptive method most used by men (90.6%) and women (75.5%). Women used double protection (53.5%) and had a fixed sexual partner (67.8%) in a greater proportion. Men, on the other hand, maintain the practice of casual relationships more frequently (70.5%) and 43.2% have already had unprotected casual relationships. Among bisexuals, condoms were the method most used by men (97.7%) and women (85.4%). In this group, 51% of women use double protection and have a steady partner (62.2%). Among homosexuals, 99.1% of gays and 46.1% of lesbians used condoms at the last sexual intercourse and 46.1% of lesbians used hormonal methods. Also, 28.8% of gays have already had an STI, a higher rate than among heterosexuals. Conclusions: There are important differences in sexual and reproductive behaviors between genders and according to the sexual orientation of young people, such as greater vulnerability to STIs among gays and lesbians, and medicalization around the female body, highlighted by the permanence of questionable practices among lesbians. Key messages: Gender issues could also explain the differences found between men and women. Differences between the sexes are also present when evaluating the use of protection against STIs or unplanned pregnancies.